(untitled) - Copeland, Tom (New York, 1994)
The book illustrates how to take advantage of the American tradition of maximizing shareholder value, demonstrates how value-based management contributes to improved strategic thinking, and shows how managers at any level can create value for their companies. In addition, this book provides: A chapter featuring insights into the strategic advantages of value-based management; strategies for multibusiness valuation, and valuation for corporate restructuring, mergers, and acquisitions; international comparisons of the cost of capital, differences in accounting procedures, and how valuation works in different countries; a detailed case study showing how valuation techniques and principles are applied.
Keywords: Corporations; Valuation